Unusual C–O bond cleavage of aromatic ethers in ruthenium complexes bearing a 2-alkoxypyridyl fragment. Issue 36 (28th August 2019) - Deng, Danfeng; Hu, Bowen; Yang, Min; Chen, Dafa
Abstract : The SN 2 C–O cleavage mechanism with neutral H2 O switches to SN Ar when KOH is added. Abstract : Two tetradentate (NNOP) ruthenium products [{RO-C5 H3 N-C5 H3 N-CH(O)-C6 H4 -PPh2 }Ru(CO)(PPh3 )]Cl (1 : R = Me;3 : R = Ph) were isolated by the reactions of the corresponding ligands with RuHCl(PPh3 )3 (CO). Complex1 could also be transformed into2 when heated in THF, through C–OMe bond cleavage. The mechanism of the unusual C–O cleavage in complex1 was investigated, and the results indicate that it is an SN 2 mechanism through the attack of trace amounts of neutral H2 O. In contrast, in the presence of KOH, the reaction switches to an SN Ar chemistry. The bidentate ruthenium isomers [CH3 O-C5 H3 N-C5 H4 NRuH(CO)(PPh3 )2 ]Cl (4a and4b ) could undergo similar C–O cleavage, affording product O-C5 H3 N-C5 H4 NRuH(CO)(PPh3 )2 (5 ), which reacted with HCl to generate complex [HO-C5 H3 N-C5 H4 NRuH(CO)(PPh3 )2 ]Cl (6 ). These complexes were tested as catalysts for β-alkylation of secondary alcohols with primary alcohols, and a series of β-alkylated 1-phenylethanol derivatives were isolated in high yields.